Canadian Sports History: Some Comments to Urban Historians - Mott, Morris (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1983)
In the last ten or fifteen years a considerable number of publications on the history of Canadian sport have appeared. The bulk of these items are of little consequence to serious scholars. A few, however, are useful and informative to urban historians. The existence of several exemplary studies on the history of sport and leisure in Great Britain and the United States, together with the current acceptance of the idea that good sports history can be good social or cultural history, should encourage more and better studies of Canadian sporting developments.